SETTLEMENT OF ANY CASES BY ADVOCATES AGAINST CLIENTS - Nendyo Agung Legowo; Hervina Puspitosari (Universitas Islam Balitar, 2023)
The client gives a control of lawyer to the advocate went with by a discourse of the rights and commitments of the parties. Advocates are entitled to an honorarium and clients are entitled to lawful help in a mindful way and in agreement with appropriate law. Article 6 of Law Number 18 of 2003 concerning Advocates (Law on Advocates) emphasizes that disregarding clients and negligance of cases may be a infringement that can be arraigned. The Advocates' Organisation Board, particularly the PERADI Territorial Organisation Board (DKD) of East Java, is authorized by the Law on Advocates to require activity and endorse advocates who are demonstrated to have damaged advocates proffesional ethics. The truth is that there are still numerous advocates who abuse the code of morals, one of which is case disregard. All through 2019-2020, 11 (eleven) cases of infringement of the code of morals were recorded by the DKD PERADI East Java. The detailing of the issue talked about is lawful cures that clients can take against.